Ergonomic Design for inclusive public spaces: a socio-demographic perspective on Chıld's ergonomıcs ın Umranıye and Kadikoy, Istanbul - Celik, Elif; Sungur, Asli; Turkyilmaz, Cigdem Canbay (TAYLOR & FRANCIS LTD, 2025)
This study employs mixed methods, integrating demographic variables to analyze public space space usage in child ergonomics Utilizing Space Syntax and Pierre Bourdieu's theory within the framework of inclusive public space, it explores the relationship and needs between ergonomics and the socio-demographic statuses of children. The research applies an analytical approach based on Bourdieu's focus on spatial capital to compare neighborhoods with varying socio-demographic characteristics in Istanbul's Umraniye and Kadikoy districts. A critical spatial analysis emerges from comparing 14 public spaces in Umraniye's Cakmak neighborhood (CS1) with a public area in Kadikoy's Suadiye neighborhood (CS2). Methodologically, the study includes weekday (day 1) and weekend (day 2) field observations, Space Syntax analysis, TSI 2022 demographic data, digital maps, and anthropometric measurements specific to children aged 7-11. This effective mixed methodology provides a notable comparative spatial examination in child ergonomics research, highlighting clear disparities between the public spaces in CS1 and CS2.
Keywords: Public space; children's ergonomics; mixed methods; bourdieu's theory; space syntax; MIXED METHODS RESEARCH; CHILD; PRINCIPLES; FRAMEWORK; SYSTEMS; FUTURE; CITIES; POLICY; CITY; Architecture; Construction & Building Technology